3-D reconstruction by extended depth-of-field in failure analysis - Case study II: Fractal analysis of interlaminar fracture in carbon/epoxy composites - de Campos, Kamila Amato [UNESP]; Augusto, Juliana [UNESP]; Pereira, Thais Abigail [UNESP]; de Oliveira Hein, Luis Rogerio [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
This work aims to evaluate the fractal behavior of fracture surfaces in laminated carbon/epoxy composite material, by conducting double cantilever beam (DCB) tests and comparing fractal values against critical (at notch region) or local (at selected positions along entire surface) interlaminar fracture toughness data. A conventional light microscope permitted to obtain ordered image stacks to get elevation maps using the extended depth-of-field method for quantitative investigation of fracture surface behavior. Also, a method to define the threshold between macro and micro scales for mixed fractal behavior was proposed, permitting to compare mono-fractal behavior with the "structural" (micro scale or low resolution) and "textural" (macro scale or high resolution) mixed fractal components. It was found a linear correlation between Mode I interlaminar fracture critical toughness (G(IC)) and "structural" fractal dimension, defined as the fractal behavior at micro scale. It suggests that the fracture surface formation in carbon/epoxy composites is highly associated to local features of the microstructure. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Extended depth-of-field; Polymer-matrix composites; Fractal fracture; Quantitative fractography; Optical microscopy